Experimental and numerical modelling of buried pipelines crossing reverse faults. Issue 114 (November 2018) - Demirci, Hasan Emre; Bhattacharya, Subhamoy; Karamitros, Dimitrios; Alexander, Nicholas
Abstract: Fault rupture is one of the main hazards for continuous buried pipelines and the problem is often investigated experimentally and numerically. While experimental data exists for pipeline crossing strike-slip and normal fault, limited experimental work is available for pipeline crossing reverse faults. This paper presents results from a series of tests investigating the behaviour of continuous buried pipeline subjected to reverse fault motion. A new experimental setup for physical modelling of pipeline crossing reverse fault is developed and described. Scaling laws and non-dimensional groups are derived and subsequently used to analyse the test results. Three-dimensional Finite Element (3D FE) analysis is also carried out using ABAQUS to investigate the pipeline response to reverse faults and to simulate the experiments. Finally, practical implications of the study are discussed. Highlights: Novel experiment setup to study pipelines crossing reverse faults. Derivation of similitude relations and scaling laws for a pipeline problem. 3D Finite Element Analysis for validation of the experimental results. Collation of field records on pile line performance for practical range of non-dimensional groups.